Unfolding the Neutron Flux Spectrum on the Surface of Mars Using the MSL‐RAD and Odyssey‐HEND Data - L. M. Martinez Sierra; I. Jun; B. Ehresmann; C. Zeitlin; J. Guo; M. Litvak; K. Harshman; D. Hassler; I. G. Mitrofanov; D. Matthiä; S. Loffler (Space Weather)
Abstract Understanding the long‐term radiation environment at the surface of Mars allows us to estimate the exposure for future robotic and crewed missions. Typically, the radiation environment includes charged particles (i.e., protons and heavier ions) and neutral particles (i.e., gamma rays and secondary neutrons). Previous studies used in‐situ measurements, models, or both to determine the characteristics of the radiation at Mars. For example, the Mars Science Laboratory instrument, the Radiation Assessment Detector (RAD), has provided invaluable in‐situ data since landing in 2012. However, the RAD instrument is only sensitive to neutrons with energies > ∼6 MeV and therefore misses what is expected to be a substantial flux of lower‐energy neutrons. To address this gap, we have developed an approach to derive the surface neutron spectrum using the MSL RAD data augmented by orbital data from the High Energy Neutron Detector (HEND) onboard Mars Odyssey (neutron energy < ∼10 MeV). Using a power law fit, we determine neutron flux spectra that reproduce the measurements recorded by both RAD and HEND. Our approach involves a series of Monte Carlo simulations to develop a set of atmospheric transmission functions that enables us to convert the on‐orbit HEND data to their corresponding surface neutron flux spectra. The combined RAD—HEND data present a unique opportunity to obtain a complete picture of the surface neutron environment.